Pengaruh Promosi dan Harga terhadap Keputusan Pembelian Skincare Brand Skintific di Kota Samarinda - Adella Rizki Salsabila; Hudyah Astuti Sudirman; Istimaroh Istimaroh (Jurnal Ilmiah Manajemen dan Kewirausahaan, 2025)
This study aims to analyze the influence of promotion and price on purchasing decisions of the Skintific skincare brand in Samarinda. Skintific, a Canadian skincare brand, has gained popularity in Indonesia since 2021 through awards and strong digital strategies. Using a quantitative approach, this study distributed questionnaires to 100 respondents who use Skintific products in Samarinda. The results of multiple linear regression analysis showed that price has a positive and significant effect on purchasing decisions, while promotion does not have a significant partial effect. However, both variables simultaneously influence purchasing decisions significantly. This indicates that consumers in Samarinda prioritize rational aspects such as price-quality alignment over promotional appeal. Although Skintific engages in promotional tactics like discounts and influencer endorsements, price perception remains a stronger factor in consumer decisions. The study underscores the importance of competitive and relevant pricing strategies and the need for tailored promotional efforts that match local preferences. It contributes to the literature on regional consumer behavior and can serve as a reference for developing effective marketing strategies in competitive and dynamic skincare markets